Association between body image dissatisfaction and depressive symptoms in adolescents - Fiorela Flores-Cornejo; Mayumi Kamego-Tome; Mariana A. Zapata-Pachas; German F. Alvarado (Brazilian Journal of Psychiatry, 2017)
Objective: To determine the association between body image dissatisfaction (BID) and depressive symptoms in adolescents from a school in Lima, Peru. Methods: A cross-sectional study was performed through a census of 875 high-school students, aged 13 to 17 years, from a school in Lima. Participants completed a survey containing the Body Shape Questionnaire (BSQ) and the Patient Health Questionnaire-9 (PHQ-9). Data regarding demographics, alcohol and tobacco use, self-esteem, and family history of depression were also obtained. To identify associated factors, Poisson regression with robust variance was used. Prevalence ratios with 95% confidence intervals were calculated. Results: Of the 875 adolescents, 55.8% were male. The mean age was 14.1±1.5 years. Depressive symptoms were observed in 19.9% of participants. An association between BID and depressive symptoms was found. Alcohol and tobacco use were also associated with the outcome of interest. Conclusions: Teens who had BID were 3.7 times more likely to report depressive symptoms. Additionally, those who used tobacco or alcohol were 1.5 and 1.4 times more likely to have depressive symptoms, respectively. Further studies targeting other populations and using longitudinal designs are recommended.